Distal turbidite fan/lobe succession of The Late Paleozoic Taean Formation, Western Korea - So, Young Seok; Rhee, Chul Woo; Choi, Pom-Yong; Kee, Weon-Seo; Seo, Jin Yeong; Lee, Eun-Ju (Geosciences journal (Seoul, Korea), 2013)
The Late Paleozoic Taean Formation is similar in depositional environment and age to sedimentary successions around the collision belt between the North and South China blocks. The studies on those successions would be helpful for figuring out the pre- and post-collision depositional setting and tectonic framework around the Korean Peninsula and mainland China. As the first step for such an approach to the Taean Formation in Anmyeondo, this study carried out analyses of sedimentary facies and architectural elements of it. The Taean Formation of turbidite origin consists of 6 sedimentary facies, which can be grouped into 4 facies associations (FA) representing axis lobes, off-axis lobes, fringe lobes and distal fringe lobes of a deep-water turbidite system. Based on assemblage and stacking pattern of 4 facies associations, three architectural elements are defined: forward stacking of depositional lobe, backward stacking of depositional lobe and fan/lobe fringe. The first two architectural elements are characterized by meso-scale thickening- and thinning-upward succession of facies associations 1 and 2. The last one is defined by disorganized assemblage of facies associations 3 and 4. Stratigraphic correlation on the level of architectural elements gives rise to division of the Taean Formation in Anmyeondo into 4 fining-upward stratigraphic units (FSUs) separated by thick mudstone beds of fan/lobe fringe architectural element. The stratigraphic units can be grouped into 2 turbidite members based on the composition of sandstone turbidite beds. The lower turbidite member A comprises FSU 1 of calcareous turbidite beds, whereas the upper turbidite member B comprises FSU 2–4 of non-calcareous turbidite beds. These sedimentological and stratigraphic features indicate that the Taean Formation in Anmyeondo represents distal fan/lobe depositional environments in a sand/mud-mixed turbidite system.